Correlation between Personal hygiene and Household Overcrowding to the Incidence of Pediculosis capitis in Sukogidri Village Jember - Warda Ayu Nadira; Erma Sulistyaningsih; Dwita Aryadina Rachmawati (Journal of Agromedicine and Medical Sciences, 2020)
Abstract Pediculosis capitis is an infection of human hair or scalp caused by Pediculus humanus var. capitis. This disease is classified as a neglected disease and is quite developed in developing and poor countries. Risk factors that influence the incidence of pediculosis capitis is the level of education of parents, socio-economy, personal hygiene, age, gender, and household overcrowding. The purpose of this study was to determine the correlation between personal hygiene and household overcrowding to the incidence of pediculosis capitis in Sukogidri Village Jember. This study was an observational analytic study, with a cross sectional approach carried out on 230 respondents in Sukogidri Village Jember. In this study, head lice was examined using crescent combs, filling in personal hygiene questionnaires, and measuring the area of ​​respondent’s house. The results showed the prevalence of pediculosis capitis in Sukogidri Village was 44.3% (102 respondents). The results of data analysis using the fisher test and chi-square test showed that personal hygiene and household overcrowding had a significant relationship (p <0.05) as a risk factor for the incidence of pediculosis capitis in Sukogidri Village Jember. Keyword : personal hygiene, household overcrowding, pediculosis capitis